PENGARUH LATIHAN BERPASANGAN TERHADAP PENINGKATAN HASIL SEPAK SILA PADA SISWA EKSTRAKURIKULER SEPAK TAKRAW DI MTS PONDOK PESANTREN MASDARUL ULUM PEMULUTAN - Tanzila; Daryono; Agung Mahendra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The background of this research is because there are still many students who have not mastered the basic techniques of sepak sila in the game of sepak takraw. This study aims to determine whether or not there is an effect of pair practice on the results sepak sila sepak takraw MTs Pondok Pesantren Masdarul Ulum. The research method used is an experimental method with one-group pretest-posttest design. The population in this study were all male students who attended the sepak takraw extracurricular activity MTs Pondok Pesantren Masdarul Ulum. Sampling using total sampling technique as many as 16 male students. The data collection technique uses a measurement test with the test sepak sila sepak takraw. The data obtained from the results of the pretest with an average value of 27.44 with a standard deviation of 6.387 while the results of the posttest obtained an average value of 38.19 with a standard deviation of 6.725. Based on the results of the t test, the tcount value is 22.713 > ttable 1,753 with a significant value of 0.000 (2-tailed) <0.05. Thus, there is an effect of pair practice on the results of sepak sila sepak takraw MTs Pondok Pesantren Masdarul Ulum..